Development and Validation of High Performance Liquid Chromatography Method for Simultaneous Estimation of Curcuminoids from Rhizome Extracts - Begum, Amrin; Nagamani, Bolla; Sridevi, Garapati (Asian Journal of Chemistry, 2017)
A rapid and sensitive liquid chromatographic method is developed and validated for the simultaneous estimation of various curcuminoids. The method was used for the estimation of curcuminoids in commercially available dosage forms, bulk and naturally available root and rhizome extracts. The separation was performed on a Phenomenex ODS 2 C18 (5 μm, 15 cm × 4.6 mm) column. The composition of mobile phase is 50:50 % (v/v) of acetonitrile and water containing 2 % v/v glacial acetic acid operated on isocratic mode at a flow rate of 1.2 mL/min. Quantitation was achieved by HPLC-UV detection at 425 nm. The specificity of the method (blank interference, interference from degradation products and interference from formulation excipients) was established. Degradation studies were performed in acid, alkaline, oxidative and photolytic stress conditions. The results showed that curcumin is prone to degradation in all aqueous media irrespective of pH of the solution. Also, in comparison to the standard curcuminoid composition (83.5 % curcumin, 14.5 % dimethoxycurcumin and 1.5 % bis-dimethoxycurcumin), large variation was observed in the root and rhizome powder extracts that were collected from commercial and crop samples.